(3eNJUQ JfHjg GdWGdH hEQTGO GdOGQS ajeG aj OeTb ef GdLhGeY hGdeOGQSs - (3YHO GdHGSW GdhGYX GdOeTbj GdYdehis; (3YHO GdbGOQ Hf eMeO Hf YeQ Hf eMeO GHf jhSa Hf YHO Gddg Hf fYje, CHh GdeaGNQ,J (B927 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf s
(3fSNI eUhQI Yf fSNI HGQjSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B301s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B133 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B237 s
Keywords: (3GdJGQjNs